Didactic knowledge of Mathematics teachers about their teaching: From the perspective of the use of Manipulative materials - Lopes, Venâncio; Ribeiro, Marcelino da Costa; Pinto, Alfredo (CV. Green Publisher Indonesia, 2025)
The main objective of this research was to explore the opinions of primary and secondary school teachers in the municipality of Manatuto regarding the teaching of Mathematics using manipulative materials. A quantitative methodology was employed, and the opinions of 30 teachers were gathered through a closed questionnaire. Data analysis was conducted using Microsoft Excel. The results indicated that primary and secondary school teachers in the municipality of Manatuto are familiar with and use the following manipulative materials in their teaching practice: Geoboards, tangram, geometric solids boxes, abacus, rulers, compasses, protractors, blackboards, logical blocks, number dice, coins, and playing cards. These materials were used for specific topics, but not across all contents outlined in the mathematics curriculum. Teachers stated that manipulative materials help students touch, feel, and move objects, making abstract concepts more concrete and understandable, which aids in student comprehension and motivation. These materials serve as symbolic representations, help contextualize learning, and promote skill development, but they require careful planning and teacher guidance to be effective. Regarding curricular guidelines, the findings suggest that mathematics programs should incorporate the use of manipulative materials to enhance the learning experience.